2022
DOI: 10.18203/2394-6040.ijcmph20222911
|View full text |Cite
|
Sign up to set email alerts
|

Perception and awareness of first year MBBS students about the subject community medicine

Abstract: Background: In India, departments of the medical discipline community medicine or preventive and social medicine began to be established in the year 1955. It plays important role in medical curriculum for imparting training as comprehensive healthcare giver at various levels of health system. This study aimed at assessing perception and awareness of first year MBBS students about the subject community medicine, before formal introduction of the discipline as a part of their medical curriculum.Methods: The cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A high proportion of first-year MBBS students (37.8%) perceived that this subject would teach about AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homeopathy) medication, whereas, 16% of students believed that this subject would not teach them anything new, apart from other subjects. One-third of the students were unaware of the subject before joining MBBS [7]. Another study revealed that 17.8% of students believed that community medicine trained them to be "community workers" and 3.4% believed that it taught nothing new.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of first-year MBBS students (37.8%) perceived that this subject would teach about AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homeopathy) medication, whereas, 16% of students believed that this subject would not teach them anything new, apart from other subjects. One-third of the students were unaware of the subject before joining MBBS [7]. Another study revealed that 17.8% of students believed that community medicine trained them to be "community workers" and 3.4% believed that it taught nothing new.…”
Section: Discussionmentioning
confidence: 99%
“…FIGURE 5: Forest plot of the meta-analysis for the willingness to take community medicine as a career option among medical students: subgroup analysis of different professional years of MBBS MBBS: Bachelor of Medicine and Bachelor of Surgery.Sources: References[7,14,15,19,24,26,27].…”
mentioning
confidence: 99%